Estudo químico e biológico de Bauhinia pulchella Benth - Carvalho, Jarbas Lima de (2014)
This present work reports the chemical and biological analysis of the stem and leaves from Bauhinia pulchella. In this study, the ethanol extract from stems was obtained by maceration, subjected to chromatographic fractionation, leading to isolation of three flavonoids: (+)-3’,4’-dihydroxyphenyl-chroman-7-ol (BP-2), (-)-fisetinidol (BP-3) and (+)-epicatechin (BP-4); a mixture of triterpenes taraxerone and β-amyrenone (BP-1); a mixture of steroids sitosterol and stigmasterol (BP-5); and a bibenzyl named 2-hydroxy-3’,5’-dimethoxybibenzyl (BP-6). It is notewhorthy to mention that BP-1 and BP-4 substances are unprecedented in the genus, while BP-2 is unpublished. Chemical structures of secondary metabolites obtained were elucidated by 1H and 13C NMR; IR and MS associated with comparison of data described in the literature. Chemical composition of the essential oil from leaves of B. pulchella, obtained by hydrodistillation, was determined and quantified by gas chromatography-mass spectroscopy (GC/MS) and gas chromatography-flame ionization detector (GC/FID), which identified 95,68% of all constituents. α-pinene (23.89%); caryophyllene oxide (22.43%) and β-pinene (12.19%) were the major components. The essential oil was tested against Aedes aegypti larvae and showed LC50 value of 105.93 ± 1.48 μg/mL. The cytotoxic activity of essential oil was evaluated on human tumor cell lines (HL-60; MCF-7; NCI-H292 and HEP-2) was evaluated, showing IC50 values with confidence intervals of 9.941 (8.238 to 12.00), 53.05 (41.39 to 67.99), 48.98 (44.22 to 54.25) and 50.42 (42.47 to 59.87) μg/mL, respectively and the cell line HL-60 the most sensitive among the cells tested. This is the first report of the chemical study of Bauhinia pulchella, as well the investigation of larvicidal activity and cytotoxicity of the essential oil from its leaves.